A Framework for Optimizing the Process of Energy Harvesting from Ambient RF Sources - Ruchi Sharma; S. Balaji (Institute of Advanced Engineering and Science, 2018)
Energy harvesting has been an active research topic in the past half a decade with respect to wireless networks. We reviewed some of the recent techniques towards improving energy harvesting performance to find that there is a large scope of improvement in terms of optimization and addressing problems pertaining to low-powered communicating mobile nodes. Therefore, we present a framework for identifying available RF sources of energy and constructing a robust link between the energy source and the mobile device. We apply linear optimization approach to enhance the performance of energy harvesting. Probabilility theory is used for identification of event loss in the presence of different number of nodes as well as node distances. The objective of the proposed system is to offer better availability of RF signals as well as better probability of energy harvesting for mobile devices. The proposed technique is also found to be computationally cost effective.